Message from A.O. [Abwehr Office] ,Kirkenes to the forces. (1943)
Message distributed to the forces concerning deserters, hostile agents, the inspection of stamp factories, and the passing of documents. Taken from microfilm Records of the German Field Command, Armies, National Archives Series T-315,Reel 109, 2d Geb. (Mtn.) Div, Tatigkeibericht, folder 45157/7, frame 000045. Translated by Major James F. Gebhardt, USA (retired)